Genetic overlap between dystonia and other neurologic disorders: a study of 1,100 exomes - Dzinovic, Ivana; Boesch, Sylvia; Škorvánek, Matej; Necpál, Ján; Švantnerová, Jana; Pavelekova, Petra; Havránková, Petra; Tsoma, Eugenia; Indelicato, Elisabetta; Runkel, Eva; Held, Valentin; Weise, David; et al. (Parkinsonism & related disorders, 2022)
Introduction - Although shared genetic factors have been previously reported between dystonia and other neurologic conditions, no sequencing study exploring such links is available. In a large dystonic cohort, we aimed at analyzing the proportions of causative variants in genes associated with disease categories other than dystonia. - Methods - Gene findings related to whole-exome sequencing-derived diagnoses in 1100 dystonia index cases were compared with expert-curated molecular testing panels for ataxia, parkinsonism, spastic paraplegia, neuropathy, epilepsy, and intellectual disability. - Results - Among 220 diagnosed patients, 21% had variants in ataxia-linked genes; 15% in parkinsonism-linked genes; 15% in spastic-paraplegia-linked genes; 12% in neuropathy-linked genes; 32% in epilepsy-linked genes; and 65% in intellectual-disability-linked genes. Most diagnosed presentations (80%) were related to genes listed in ≥1 studied panel; 71% of the involved loci were found in the non-dystonia panels but not in an expert-curated gene list for dystonia. - Conclusions - Our study indicates a convergence in the genetics of dystonia and other neurologic phenotypes, informing diagnostic evaluation strategies and pathophysiological considerations.
Available online 18 July 2022
Gesehen am 01.02.2023